Supply Chain Management – Factor of Increased Firms Competitiveness - Cristinel Vasiliu (Amfiteatru Economic)
In light of frequent economic changes companies are faced with the need ofadopting new approaches towards the market. Old, classical methods oftenprove to be inadequate and, once successful companies are now facing greatdifficulties. Proof of this are the mergers within the automotive andtelecommunications business segments, reconfiguration of these marketsand repositioning of their leaders.